Budgeting Basics for New Academic Chairpersons - N. Douglas Lees; David J. Malik; Jane R. Williams (Academic Chairpersons Conference Proceedings, 2019)
The session is geared to new chairpersons who have little or no experience with budgets. Emphases will be placed on working with the dean to create fiscal flexibility and to incentivize budget expansion.
Keywords: Budgets; Higher Education; Academic Departments; New Chairpersons